A study of indications and assessment of fusion rates for atlantoaxial subluxation - Reddy, A. Mastan; Faisal, Gulam Mustafa; Jyothi, Sangam M. (International Surgery Journal, 2016)
Background: Stabilization of the atlantoaxial articulation presents special problems due to the unique anatomical and functional characteristics of the upper cervical vertebra. The majority of rational movements occur at C1-C2; the cervical stabilization limits rational movement of the neck. The objective of the study was to assess the fusion rates using different techniques of atlantoaxial arthrodesis. Methods: All the patients who were operated for atlantoaxial stabilization in the department of neurosurgery, between December 2012 and March 2015 formed the study group. Demographic data, detailed history of symptoms and other morbidities were recorded. Routine hematological and biochemical parameters were assessed. Imaging features like X-ray c spine {neutral, flexion & extension view}, CT scans C-spine, and MRI C-spine was used. The anatomic characteristics of cervicovertebral junction, presence of ventral or dorsal compression and atlantoaxial stability were noted. Operative details like types of approach, whether dorsal wiring or screw fixation or both were noted. Results: Twelve patients had anterior displacement of the atlas on the axis averaging 9.6 mm. Five had posterior displacement averaging 9.2 mm. More than 2/3 of patients had preserved motor function, grade D according to Frankel Classification. More than 60% patients had difficulty in walking and required support to walk. Most of the patients presented with long tract signs and objective weakness. Most common procedure done was C1 lateral mass and C2 pedicle screw fixation. The next common procedure performed was C1-C2 fusion with Sub laminar wiring using titanium wires. There was no mortality. Conclusions: There is no best method for OCF, and the method of surgery should be bases on the type of instability, the integrity of posterior cervical elements, the extension of decompression, co morbidities, individual anatomic variation, and the surgeon’s familiarity with the techniques.